2013
DOI: 10.1016/j.jedc.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Zipf's law and maximum sustainable growth

Abstract: Zipf's law states that the number of firms with size greater than S is inversely proportional to S. Most explanations start with Gibrat's rule of proportional growth but require additional constraints. We show that Gibrat's rule, at all firm levels, yields Zipf's law under a balance condition between the effective growth rate of incumbent firms (which includes their possible demise) and the growth rate of investments in entrant firms. Remarkably, Zipf's law is the signature of the long-term optimal allocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 47 publications
5
69
0
Order By: Relevance
“…The model suggests that a lognormal size distribution with a power law tail must always occur when elements of an economic system growth with a small mean growth rate and large growth rate fluctuations. Since size distributions similar to the bank size distribution can be often found in social systems (Bouchaud and Mezard 2000, Gabaix 2008, Malevergne et al 2013 it can be expected that its origin can be explained analogous to the presented model.…”
Section: _________________________ 3 Conclusionsupporting
confidence: 62%
“…The model suggests that a lognormal size distribution with a power law tail must always occur when elements of an economic system growth with a small mean growth rate and large growth rate fluctuations. Since size distributions similar to the bank size distribution can be often found in social systems (Bouchaud and Mezard 2000, Gabaix 2008, Malevergne et al 2013 it can be expected that its origin can be explained analogous to the presented model.…”
Section: _________________________ 3 Conclusionsupporting
confidence: 62%
“…The superposition of distributions has a neat interpretation: it corresponds to considering entities that are born successively. Combining the features of birth and stochastic proportional growth has been considered in [23,33,34]. Our model can be viewed as the simplest and purest incarnation of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to examine dependence among entities in three particular different classes: complete independence; Kesten dependence (a dependence based on the Kesten process); and mixed dependence, combining both independence and Kesten dependence. Rather than studying the cross-section at a given time of the sizes of entities present in the system (as done, e.g., in [23,33,34]), we study the distribution of the sum of sizes of all entities in the system. This corresponds to the total capitalization of a country, when entities are firms, or to the total biomass of an ecosystem for biological populations.…”
Section: Introductionmentioning
confidence: 99%
“…It could be shown that, to a large extent, the characteristics of the distribution of initial sizes is irrelevant to the shape of the upper tail of the steady-state distribution of entities [30].…”
Section: Modelmentioning
confidence: 99%
“…Malevergne et al [30] also provided the explicit functional relationship between the power-law exponent and its key parameters, predicting deviations from Zipf's law due to various sources (see equation (4) below).…”
mentioning
confidence: 99%